N3P. (Groningen : Stichting Niggendijker, 2001)
Overzicht tentoonstellingen 1999
Bik, Liesbeth ; Bosch, Karin ; Boumans, Jean ; Clijsen, Teske ; Conijn, Joost ; Derksen, Christel ; Doctor Broadcast ; Doornbos, Lars ; van Grunsven, Jan ; Hobijn, Erik ; Horst, Jop ; IJspeerd, Michel ; Kaap, Gerald Van Der ; Van Kerkvoorde, Marcel ; Knutz, Eva ; Komen, A.P. ; van der Kooij, Heerko ; van Kooij, Rijk ; Kool, Renée ; Kuiper, Elmar ; Kunzmann, Stefan ; Lautenbach, Sjoerd ; Marks, Gabriëlle ; van Meer, Aldje ; Van Meerendonk, Theo ; Meijer, Michel ; Mertens, Pierre ; Monfeldt, Magnus ; Müller, Gijs ; Müller, Marc ; Muñoz, Begoña ; Murphy, Karen ; N 28 ; Nussbaum, Martina ; Oldenburger, Wopke ; Olofsen, Erik ; van der Pol, Jos ; de Rijke, Jeroen ; de Rooij, Willem ; Sagel, Reinier ; Scheerder, Sasker ; Slecht, Bar ; Speakman, William ; Stel, Peter ; Terpstra, Martin ; Tyler, Mike ; Verbruggen, Jan ; Vroom, Arjan ; van Weelden, Willem ; Wie, Eric ; Wolf, Niels ; Yee Ling Tang ; Zijp, Ivonne
Nederlands
boek